Reduction of Vehicle-Induced Vibration of Railway Bridges due to Distribution of Axle Loads through Track - Zhibin Jin; Bo Huang; Juanjuan Ren; Shiling Pei (Shock and Vibration)
Short span railway bridges are prone to resonate caused by dynamic train axle loads, which were usually modeled as moving point loads on the bridge in many numerical studies. In reality, the axle weight of the train is a spread load for the bridge deck because of the transfer of the track structure. Previous numerical studies indicated that the spread axle load distributed through the track structure significantly reduces bridge responses compared to the point load model. In this study, the reduction effect is investigated analytically by solving the moving load problem for both the point load and the spread load cases. The analytical solution reveals that bridge responses from the spread load model can be obtained by filtering bridge responses from the point load model. The filter function is exactly the Fourier transform (FT) of the load spreading function. Based on this relationship, a reduction coefficient reflecting the load spreading effect on bridge responses is derived. Through numerical examples, the accuracy of this proposed reduction coefficient is validated not only for the moving load models but also for vehicle-bridge interaction (VBI) problems.